On the citizen - Hobbes, Thomas, 1588-1679, (Cambridge texts in the history of political thought., 1998)
De Cive (On the Citizen) is the first full exposition of the political thought of Thomas Hobbes, the greatest English political philosopher of all time. Professors Tuck and Silverthorne have undertaken the first complete translation since 1651, a rendition long thought (in error) to be at least sanctioned by Hobbes himself. On the Citizen is written in a clear, straightforward, expository style, and in many ways offers students a more digestible account of Hobbes's political thought than the Leviathan itself. This new translation is both accurate and accessible, and is itself a significant scholarly event: it is accompanied by a full glossary of Latin terms, a chronology, bibliography, and an expository introduction. Throughout the editors have emphasised consistency in the translation and usage of Hobbes's basic conceptual vocabulary, respecting Hobbes's own concern for accurate definition of terms.